2014
DOI: 10.1371/journal.pone.0087236
|View full text |Cite
|
Sign up to set email alerts
|

New Material of Beelzebufo, a Hyperossified Frog (Amphibia: Anura) from the Late Cretaceous of Madagascar

Abstract: The extant anuran fauna of Madagascar is exceptionally rich and almost completely endemic. In recent years, many new species have been described and understanding of the history and relationships of this fauna has been greatly advanced by molecular studies, but very little is known of the fossil history of frogs on the island. Beelzebufo ampinga, the first named pre-Holocene frog from Madagascar, was described in 2008 on the basis of numerous disarticulated cranial and postcranial elements from the Upper Creta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 143 publications
(311 reference statements)
0
51
0
1
Order By: Relevance
“…Hyperossification is common in anuran fossils (possibly because hyperossified elements are more likely to be preserved in the fossil record) and is present in putative archeobatrachians, mesobatrachians, and neobatrachians (58). Identifying the phylogenetic placement of these fossil taxa is challenging because the material is often fragmentary, and hyperossification seems to result in artificial groupings based on homoplastic features (44,59,60), despite the differences in shape identified across hyperossified species in our study. Our results corroborate these previous findings: Hyperossification likely has evolved multiple times across crown-group anurans, leading to increased rates of shape evolution.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hyperossification is common in anuran fossils (possibly because hyperossified elements are more likely to be preserved in the fossil record) and is present in putative archeobatrachians, mesobatrachians, and neobatrachians (58). Identifying the phylogenetic placement of these fossil taxa is challenging because the material is often fragmentary, and hyperossification seems to result in artificial groupings based on homoplastic features (44,59,60), despite the differences in shape identified across hyperossified species in our study. Our results corroborate these previous findings: Hyperossification likely has evolved multiple times across crown-group anurans, leading to increased rates of shape evolution.…”
Section: Discussionmentioning
confidence: 83%
“…Our framework will be useful in subsequent paleobiological studies of fossil frogs, especially when the 3D structure of the skull is recoverable. For example, Baurubatrachus pricei from the Late Cretaceous of Brazil (60), Beelzebufo ampinga from the Late Cretaceous of Madagascar (44), and Thaumastosaurus gezei from the Eocene of France (61) possess hyperossified, wide skulls with a posteriorly shifted jaw joint and bony articulation between the squamosal and maxilla, suggesting that these frogs specialized on eating relatively large, vertebrate prey.…”
Section: Discussionmentioning
confidence: 99%
“…Research in paleontology carried out in Madagascar revealed Cretaceous birds, amphibians, snakes, and mammals. The peculiar Beelzebufo from the Upper Cretaceous (100.5-66 Ma) of western Madagascar was a giant frog more closely related to extant frogs present in South America but absent from Madagascar [7]. The Mesozoic (251.902-66 Ma) snakes recovered in Madagascar belong to an extinct family [8], while the modern mammals currently occurring in Madagascar have no ancestors among the known paleontological records.…”
Section: Forests and Biodiversitymentioning
confidence: 94%
“…Thaumastosaurus was therefore regarded as an anuran with South American affinities ('ceratophryines' being restricted to South America). Thereafter, such biogeographical affinities were supported by Roček and Lamaud (1995), Rage and Roček (2007), Evans et al (2008Evans et al ( , 2014 and Agnolin (2012). Roček and Lamaud (1995) provided the first detailed description of Thaumastosaurus bottii, based on various skull bones from La Bouffie, a late Eocene (MP 17) locality in the Phosphorites.…”
Section: Family Indeterminatementioning
confidence: 94%